Project-Based Learning with Virtual Laboratories to Promote Higher-Order Thinking Skills to Achieve Competency in Chemical Separation - Situmorang, Manihar; Mahrani, Mita; Simanjuntak, Hendra; Purba, Jamalum; Sinaga, Marudut; Sitorus, Marham; Sudrajat, Ajat (Indian Journal of Pharmaceutical Education and Research)
Background: Higher-order thinking skills become life skills for pharmacists and scientists that are needed in solving scientific problems and can be obtained through implementing appropriate learning models. Objectives: The research aims to implement a project-based learning with virtual laboratory to build higher-order thinking skills as a strategy for achieving chemical separation competence. Materials and Methods: The study was conducted involving 98 undergraduate students, devided into experimental and control groups. The research stages include developing and standardizing a project-based learning integrated virtual laboratory, implementing the model in the class and evaluating learning outcomes. Results: An innovative learning model equipped with learning resources is available for teaching separation chemistry. The developed model has been convincing effective in facilitating students’ active learning and guiding students to complete project assignments. Students are directly involved in implementing their projects contextually, namely separating target analytes, reporting and presenting project products. Thinking skills have been developed, including solution thinking, analytical thinking, evaluation thinking and creating abilities. Students learn thoroughly in achieving chemical separation competencies. The achievement score of thinking skills obtained in the experimental group was higher than that obtained in control class, learning outcomes in the experimental group were higher than the control group. The high normalized gain obtained in the experimental group proves the effectivity of the model in improving learning outcomes. Conclusion: The project-based learning model with a virtual laboratory facilitates students’ active learning, builds higher-order thinking skills and effectively improves chemistry learning outcomes as a strategy for achieving separation chemistry competence.
Keywords: Higher-Order Thinking Skills; Project-based learning; Virtual Laboratory; Separation Chemistry; StudentsStudents’ competence.